Pengaruh Norma Sosial dan Kepercayaan Kepada Pemerintah terhadap Kepatuhan Wajib Pajak - Silaen, Yosep Harry Kristian; Helmy, Herlina (Universitas Negeri Padang, 2024)
The purpose of this study is to determine whether social norms at KPP Pratama Padang have an impact on individual taxpayer compliance. This research aims to examine the influence of social norms and trust in the government on taxpayer compliance. This type of research data uses primary data. Primary data was obtained from questionnaires filled out by respondents. The sample used in this research was 399 individual taxpayers, both employees and workers in the city of Padang. The statistical data analysis technique used in this research is multiple regression analysis. The results of this research show that social norms and trust in the government have a positive effect on taxpayer compliance. The implication of this research is that the Tax Service Office needs to take steps in a positive context, such as by conducting outreach to taxpayers so that it can encourage taxpayers to comply with tax regulations that have been determined by the government, increase trust in the government implemented by the tax authority and increase sanctions. taxation given to taxpayers in order to make taxpayers comply with specified tax obligations.